The Influence of Health Education About Anemia on The Knowledge and Attitudes of Female Adolescents at SMP Negeri 2 Majene - immawanti, immawanti (Universitas Sulawesi Barat, 2025)
Anemia is a condition when the number of red blood cells or hemoglobin levels in the blood is below normal values. Anemia is caused by several factors, namely iron deficiency, vitamin B12 deficiency, and folic acid. The impact of anemia experienced by adolescent girls will make them feel tired, can reduce memory abilities, thereby affecting suboptimal academic achievement. This study aims to determine the effect of health education about anemia on the knowledge and attitudes of adolescent girls at SMP Negeri 2 Majene. The type of research used is quantitative using a pre-experimental method with a one-group pre-test post-test design. The number of samples was 51 female students of SMP Negeri 2 Majene who met the inclusion criteria using the stratified random sampling method, data were collected through a questionnaire on the knowledge and attitudes. Based on the results of the Wilcoxon Signed Ranks Test, namely 0.000 for knowledge and 0.000 for attitudes, where the results are smaller than <0.05, so there is an increase in knowledge and attitudes after being given health education. Conclusion: This study demonstrates the influence of health education about anemia on the knowledge and attitudes of adolescent girls at SMP Negeri 2 Majene. Recommendation: The school recommends that health education be conducted regularly to prevent anemia.